Transformasi sumber daya manusia untuk mendongkrak ekonomi global dan pendidikan berkualitas - Latifah, Nurul (Maliki Interdisciplinary Journal, 2025)
This study examines the low human resources in Indonesia. The goal is to find out the very basic causes of the low human resources in Indonesia. This study uses a literature review method. This method is a combination of several relevant articles, journals, and websites from various sources to gain a deeper understanding related to the low human resources in Indonesia. The findings show that the most basic factor causing the low human resources is due to the weak education in Indonesia, especially in the 3T (underdeveloped, outermost and remote) areas. With this, the government should prioritize the areas in the 3T Region first. Then there are several strategies in improving education in the 3T Region: by adding and improving all the educational facilities needed. In addition, the government must also add teaching staff. In addition to education, the government must also improve the economy in the 3T regions by building telecommunications infrastructure and internet access to the 3T regions.